2014
DOI: 10.1016/j.chom.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Targeting of a Common Host Protein-Network by Pathogen Effectors from Three Kingdoms of Life

Abstract: SUMMARY While conceptual principles governing plant immunity are becoming clear, its systems-level organization and the evolutionary dynamic of the host-pathogen interface are still obscure. We generated a systematic protein-protein interaction network of virulence effectors from the ascomycete pathogen Golovinomyces orontii and Arabidopsis thaliana host proteins. We combined this dataset with corresponding data for the eubacterial pathogen Pseudomonas syringae and the oomycete pathogen Hyaloperonospora arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
437
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(473 citation statements)
references
References 47 publications
29
437
2
Order By: Relevance
“…Functional enrichment analysis indicated that development and defense are the most prominent themes in this subnetwork. These two themes were also observed in a conserved Arabidopsis PPI network targeted by effectors of pathogens from three kingdoms of life (Weßling et al, 2014). This shared subnetwork between PTI and ETI might contribute to the coordination of different biological processes by linking together relatively separated network modules to promote plants change their state from development to defense.…”
Section: Identification Of a Shared Subnetwork Between Pti And Etimentioning
confidence: 83%
“…Functional enrichment analysis indicated that development and defense are the most prominent themes in this subnetwork. These two themes were also observed in a conserved Arabidopsis PPI network targeted by effectors of pathogens from three kingdoms of life (Weßling et al, 2014). This shared subnetwork between PTI and ETI might contribute to the coordination of different biological processes by linking together relatively separated network modules to promote plants change their state from development to defense.…”
Section: Identification Of a Shared Subnetwork Between Pti And Etimentioning
confidence: 83%
“…Recently, G. orontii effector candidates (OECs) were analyzed for their interaction with host Arabidopsis proteins. Yeast two-hybrid screening revealed that 23 OECs interact with the Arabidopsis transcription factor TCP14, and among them, 15 were localized in the nucleus (Weßling et al, 2014). Our original search found that only four out of 15 OECs that localized in the nucleus are predicted to have an NLS when analyzed with NLS Mapper (http://nls-mapper.…”
Section: Discussionmentioning
confidence: 99%
“…iab.keio.ac.jp/cgi-bin/NLS_Mapper_form.cgi; Kosugi et al, 2009). Although ADF4 was not identified as an interactor with OECs by Weßling et al (2014), the OECs used in their analysis were identified from a complementary DNA (cDNA) library generated from isolated haustoria and chosen for their possession of canonical secretion peptides (Weßling et al, 2012(Weßling et al, , 2014). In contrast, the Bgh effectors AVR a10 and AVR k1 do not have canonical secretion peptides, although their functionality in the host cytoplasm has been demonstrated (Ridout et al, 2006;Shen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…tuberosum (Simko et al, 2004a), StVe and StoVe1 from S. torvum , mVe1 from Mentha longifolia (Vining and Davis, 2009), Vr1 from Lactuca sativa (Hayes et al, 2011), VvVe from Vitis vinifera (Tang et al, 2016) and GbVe, Gbve1, Gbvdr5 and Gbvdr3 from Gossypium barbadense Yang et al, 2014;Zhang et al, 2011;Zhang et al, 2012 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, interfamily transfer of Ve1 from tomato to Arabidopsis resulted in Verticillium resistance in the latter species Zhang et al, 2014), implying that the underlying immune signalling pathway is conserved . So far, several Ve1 homologs were identified within the Solanaceae family (in wild relatives of tomato and eggplant and in cultivated potato; Chai et al, 2003;, as well as outside this 1 family (mint, lettuce, cotton and grape; Vining and Davis, 2009;Hayes et al, 2011;Zhang et al, 2011;Zhang et al, 2012;Yang et al, 2014;Chen et al, 2017). Through comparative population genomics, the V. dahliae effector protein that is recognized by the tomato Ve1 immune receptor was identified as Ave1 (for Avirulence on Ve1 tomato) .…”
mentioning
confidence: 99%